Enhancing the rectification effect of hydrogel-based stretchable ionic diodes through incorporating cations with high valence - Pengfei Xu; Xia Wu; Zefang Zhang; Peng Pan; Xinyu Liu (Microsystems & Nanoengineering)
Abstract The controlled migration of ions in biological systems has inspired the development of ion-based electronics. Ionic diodes, leveraging ions as charge carriers, offer selective control over ion flux, mimicking ion-selective behavior observed in biological systems. Conventional ionic diodes containing fluids encounter challenges in adapting to biological systems due to their limited stretchability and stability. Recent advancements in solid-state ionic diodes based on stretchable gels enable tissue-like stretchability while maintaining diode-like performance. However, their relatively low rectification ratio hinders their electrical performance, necessitating effective strategies to enhance the rectification effect of stretchable ionic diodes. Here, we propose a method to enhance the rectification effect of hydrogel-based stretchable ionic diodes by incorporating high-valence cations into the P-type hydrogel layer. Through neutralization reactions, cations with valences of 1, 2, and 3 were introduced to replace original hydrogen ions in the hydrogel, resulting in a substantial increase in the rectification ratio from 3 to over 70, with an elevated rectification ratio (140) under 100% strain. The enhanced rectification effect enables applications in iontronics, such as ionic rectifiers and bipolar junction transistors (BJTs). This study, for the first time, highlights the potential of improving electrical performances of iontronics through the manipulation of different ion properties.